Performance of Endocarditis-Specific Risk Scores in Surgery for Infective Endocarditis - Wang, Tom Kai Ming; Pemberton, James (The Thoracic and Cardiovascular Surgeon, 2018)
Background Risk models can play an important part in the decision-making of surgery for infective endocarditis, but they remain underutilized. Several endocarditis-specific risk models have been recently published with the aim to improve on existing general cardiac surgery scores such as EuroSCORE. We compared their prognostic utility of mortality and morbidities for infective endocarditis surgery.Methods The additive Society of Thoracic Surgeon's (STS) Endocarditis score, Costa score, De Feo-Cotrufo score, and Pulsuse score were calculated for consecutive patients undergoing cardiac surgery for active infective endocarditis during 2005 to 2011 at Auckland City Hospital and their discriminative value for adverse outcomes assessed.Results Mean scores for 146 endocarditis surgery patients with operative mortality 6.8% (10) were additive STS score: 32.2 ± 13.5, Costa score: 12.0 ± 6.8, De Feo-Cotrufo score: 14.6 ± 9.2, and Pulsuse score 2.2 ± 1.3. Areas under curve and 95% confidence intervals for operative mortality were 0.699 (0.534–0.865), 0.596 (0.426–0.765), 0.744 (0.590–0.899), and 0.673 (0.510–0.836), respectively. All four scores could also discriminate mortality during follow-up and composite morbidity, with the De Feo-Cotrufo score having the best overall performance.Conclusion Endocarditis-specific risk models had moderate discrimination of operative mortality and most postoperative complications, and the De Feo-Cotrufo score is the preferred score to advise clinical decisions in this setting.
Keywords: endocarditis; statistics; surgery; complications